Specimen Adequacy and Clinicopathological Evaluation of Inflammatory Bowel Disease Colorectal Biopsies in Cipto Mangunkusumo Hospital Jakarta - Lydia Kencana; Nur Rahadiani; Marini Stephanie; Diah Rini Handjari; Ening Krisnuhoni (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Background: Colorectal mucosal biopsies account for majority of daily practice specimens in the field of gastrointestinal pathology. Most of them were sent for inflammatory bowel disease (IBD) evaluation. Due to broad spectrum of histologic findings and different stage of disease, pathologists often find difficulties on calling out diagnosis of IBD. This study aims to evaluate the adequacy of specimen, clinical characteristics, endoscopy and histologic findings of colorectal biopsies from IBD and non-IBD patients.Method: This cross-sectional study included 49 IBD and 49 non-IBD cases registered in the archives of Anatomical Pathology Department, Cipto Mangunkusumo National Referral Hospital Jakarta in 2019. The samples were evaluated for adequacy of specimen, clinical, endoscopy and histologic findings.Results: Most samples were adult with a slight female predominance. All request forms contained the clinical working diagnosis but only 26.5% and 20.4% of them provided clinical history and endoscopy findings. During histology evaluation, 59.2% of the specimen was considered sub-optimal. The most common histologic findings in both IBD and non-IBD groups were diffuse lymphoplasmacytic infiltration in the lamina propria and crypt distortion. Fibrosis/collagen deposition was found in 38.8% of IBD population compared to 12.2% of non-IBD population (p=0.003). Most IBD cases (55.1%) were categorized as active phase IBD.Conclusion: Since the most common histologic findings in IBD patients were also found in non-IBD patients, IBD diagnosis based on histopathology alone is highly inadvisable. However, there were also lack of clinical data and endoscopy findings in most of colorectal biopsies sent for IBD evaluation. Along with overlapping and unspecific morphology and suboptimal events during histological evaluation, all of this complicated the diagnosis of IBD. Hence multidisciplinary approach is required for a better IBD diagnosis and treatment.